THE FREEDOM OF CONTRACT PRINCIPLE IN CONTRACT OF EMPLOYMENT - Dede Agus; Aceng Asnawi Rohani; Achmad Jaelani; Mentari Jasitisia; Beni Prawira Candra Jaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to examine the application of the principle of freedom of contract within employment contracts. The employment contract serves as the foundational agreement between an employee and an employer. As a type of contract, the employment contract inherently adheres to the principle of freedom of contract. This research employs a normative juridical method, utilizing secondary data and descriptive qualitative analysis. The findings indicate that while the principle of freedom of contract applies to employment contracts, its scope is limited by specific material and formal requirements outlined in Law No. 13 of 2003 concerning Manpower. The principle functions effectively when both parties possess equal bargaining power; however, when there is a disparity, such as the unequal socio-economic status between the employer and the employee, the principle’s application may be hindered, potentially disadvantaging the employee.